Ecology and control of the greater bandicoot rat (Bandicota indica bechstein) in rice field, Jitra, Kedah, Malaysia - Burhanuddin, Maisarah (2023)
For the safety and security of food, a science-based pest rodent management strategy is crucial. However, after 80 years of introduced in Malaysia, there were limited information obtained regarding rodent pest status in especially the greater bandicoot rat species, which put farmers at disadvantage especially with the increasing encounter of the species recently. This thesis conferring basic information upon their population abundance in the rice field, and identify the key habitat structure that affects rodent pest populations by investigating the relationships of rodent pest populations with habitat characteristics. The greater bandicoot rat (Bandicota indica), the rice field rat (Rattus argentiventer), and the black rat (Rattus rattus), were found to coexist in the rice fields of Kedah, Northern Peninsular Malaysia. The greater bandicoot rat population was found to adapt similar strategy with the rice field rat by synchronizing their breeding season with monsoonal season. Although the species responded well with protein-based bait, their stomach content was consisting of plant materials (±60%). Aside from that the rodent abundance in the rice fields was positively correlated with bund height and width, rice growing stages, and rice planting seasons (Mallows CP=526.30, Adjusted R2=16.54). However, rodent abundance was negatively related with the distance between active burrows to residential areas (Mallows CP=706.87; Adjusted R2= 4.10). The greater bandicoot rats were thought to reproduce underground and rarely respond to traps during the major rice planting season (monsoonal season). The efficacy of B. indica towards first and secondary anti- coagulant rodenticide was evaluated and there was no sign of resistance of the species during the study. Therefore, we recommend local farmers to conduct rodent control from the end of wet season until the beginning of the supplementary season (dry planting season) as it coincides with the emergence of juvenile generations bred during previous wet seasons. Authorities should conduct vigilant monitoring to avoid any new invasion to nearby states.